Policy Modeling Consistency index-based study on policy synergy for sustainable artificial intelligence in China’s digital cultural industries - Chen Qu; Xinyang Zhao (PLoS ONE, 2026)
This paper applies the Policy Modeling Consistency (PMC) index model to quantitatively evaluate 32 Chinese policies (2016–2025) promoting artificial intelligence (AI) in digital cultural industries (DCIs). Focusing on policy synergy for sustainable AI, the analysis assesses ten primary variables—including policy objectives, instruments, sustainability integration, and application levels—across national and local initiatives. Results reveal an overall ‘Excellent’ average PMC score, indicating robust policy design in economic or technological domains. However, some low-grade policies prioritize short-term regulation over sustainable governance. The study recommends embedding ‘human-centricity’ and ‘ethical risk assessment’ in sustainability indicators, alongside cultural diversity safeguards (e.g., algorithmic support for intangible heritage). These optimizations can reframe AI as a socio-cultural enabler—not merely a technical tool—advancing equitable, innovative, and ecologically resilient DCIs aligned with Sustainable Development Goals (SDGs).